Cost-Effectiveness of Length of Stay of Intravenous Aminophylline and Nebulized Salbutamol in Asthma Exacerbations - Lorensia, Amelia; Ikawati, Zullies; Andayani, Tri Murti; Maranatha, Daniel (Journal of Tropical Pharmacy and Chemistry, 2024)
Asthma is a heterogeneous disease which is also one of the major health problems in the world. Uncontrolled asthma symptoms will exacerbate asthma, which is the biggest cause of the patient into the ER. Salbutamol is a bronchodilator that belonged to the short-acting beta-2 agonist (SABA), which is an obligatory choice in the management of asthma exacerbations. Unlike the aminophylline group in Indonesia which is still often used widely and rarely appear in the side effects of its use. The main objective of this study was to evaluate the cost-effectiveness of nebulized salbutamol versus intravenous aminophylline for reduction in asthma symptoms, improvement in lung function, and a long hospital stay. The study involved 57 adults asthma exacerbation patients without complication who received treatment in the ER, were studied by using quasi-experimental methods in this study cost-effectiveness analysis to compare intravenous aminophylline (n:27) versus nebulized salbutamol (n:30) therapy to determine the most cost-effective. Intravenous aminophylline therapy was more cost-effective than nebulized salbutamol in reducing the symptoms of asthma and PEF value improvement. Clinical outcome of the length of hospital stay outcome both had the same effective, and cost analysis results showed intravenous aminophylline (US$5.38) cheaper than nebulized salbutamol (US$5.71). intravenous aminophylline was more effective in reducing asthma symptoms than nebulized salbutamol (Pvalue=0.001). Meanwhile, the average decrease in lung function intravenous aminophylline than nebulized salbutamol, although not significantly different (Pvalue=0.507). Aminophylline therapy was more cost-effective in reducing asthma symptoms and improvement in lung function compared nebulized salbutamol in exacerbations asthma patients. But cost-effectiveness researchers need to measure substance abuse outcomes in terms of Quality-Adjusted Life Years (QALY), as this will make their findings more relevant to the development of treatment policy.